Targeting SARS-CoV-2-Platelet Interactions in COVID-19 and Vaccine-Related Thrombosis - Cox, Dermot (Frontiers in Pharmacology, 2021)
It is clear that COVID-19 is more than a pneumonia and is associated with a coagulopathy and multi-organ failure. While the use of anti-coagulants does reduce the incidence of pulmonary emboli, it does not help with survival. This suggests that the coagulopathy is more likely to be platelet-driven rather than thrombin-driven. There is significant evidence to suggest that SARS-CoV-2 virions directly interact with platelets to trigger activation leading to thrombocytopenia and thrombosis. I propose a model of multiple interactions between SARS-CoV-2 and platelets that has many similarities to that with Staphylococcus aureus and Dengue virus. As platelet activation and thrombosis are major factors in poor prognosis, therapeutics that target the platelet-SARS-CoV-2 interaction have potential in treating COVID-19 and other virus infections.